Phyto therapeutic potential of Andrographis paniculata and Catharanthus roseus extract against colorectal cancer HCT-116 cell line - Rifai , Fauziah Novita Putri; Hidayah, Nurul; Prabowo, Adam; Pradani, Lisa Nahdalia (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2025)
Colorectal cancer (CRC) is the third most common cancer globally and the second leading cause of cancer-related mortality, with over 1.9 million new cases and 935,000 deaths reported in 2020. Despite therapeutic advances, recurrence, drug resistance, and systemic toxicity remain major challenges. Natural products withantioxidant and cytotoxic activity are increasingly investigated as complementary therapies. Andrographis paniculata (Sambiloto), rich in andrographolide, exerts anticancer effects by inducing apoptosis, inhibiting migration and invasion, and modulating PI3K/Akt and NF-κB signalling pathway. Catharanthus roseus (TapakDara) produces vinca alkaloids, including vincristine and vinblastine, which inhibit microtubule polymerization and are widely used in chemotherapy. Combining these extracts may enhance efficacy and reduce toxicity through synergistic interactions. This in vitro study assessed the cytotoxic and synergistic effectsof A. paniculata extract (APE) and C. roseus extract (CRE) on HCT-116 colorectal cancer cells. Extracts were prepared by ethanol maceration, and cytotoxicity was evaluated using the MTT assay at concentrations ranging from 5 to 100 μg/mL. IC₅₀ values were calculated using linear regression, and the combination index(CI) was determined at 1, 1/2 and 1/4 IC₅₀ to evaluate synergism. APE and CRE exhibited comparable cytotoxicity, with IC₅₀ values of 90 μg/mL and 89.5 μg/mL, respectively. The combination treatment revealed synergistic effects (CI <1) at multiple ratios, particularly at 1/4 IC₅₀ (CI = 0.58), demonstrating enhancedcytotoxicity at reduced concentrations. Both APE and CRE demonstrated significant cytotoxic effects against HCT-116 cells. Their combination produced synergistic interactions, suggesting potential as complementary phytotherapeutic agents for CRC with the benefits of dose reduction and minimized toxicity. Further in vivo and mechanistic studies are warranted.